Road safety survey 2009 - Swedish Road Administration (Swedish Transport Administration, 2013)
This is the 28th study in a series of annual surveys on road safety conducted since 1981. The study is conducted by Statistics Sweden on behalf of the the Swedish National Road Administration and aims to identify and analyse traffic safety statistics. Since 2010 the study is conducted on behalf of the Swedish Transport Administration.

The study is is done by a questionnaire directed to a stratified sample of the population. The study from 2009 had a 60 percent response rate and a sample of 11 096 randomly selected people aged between 15 and 84 years.

The questions in the study include, for example, traffic behaviour and traffic patterns; attitudes to road safety and traffic rules, the relation between alcohol and traffic and child safety in traffic. Both motor traffic, bicycle and foot traffic is concerned. A total of 29 questions are used, including descriptive questions, estimation questions and attitude questions.

Purpose:

The survey aims to identify and analyse traffic safety statistics.

Detta är den 28:e studien i en serie av årliga undersökningar om trafiksäkerhet som genomförts sedan 1981. 2009 års studie har har utförts av Statistiska centralbyrån på uppdrag av Vägverket och syftar till att ta fram och analysera trafiksäkerhetsstatistik. Sedan 2010 utförs studien av Trafikverket.

Undersökningen genomförs genom ett frågeformulär riktad till ett stratifierat urval av Sveriges befolkning. Förutom den pappersenkät som användes fanns också möjlighet att besvara frågeformuläret på webben. Svarsfrekvensen var 60 procent för urvalet 11 096 slumpmässigt utvalda personer i åldrarna 15 till 84 år.

Frågorna i studien behandlar bland annat trafikbeteende och trafikvanor, både hos sig själv och andra, inställning till trafiksäkerhet och trafikregler, relationen mellan alkohol och trafik samt barns säkerhet i trafiken. Både motortrafik, cykel och gångtrafik berörs. Totalt används 29 stycken frågor som består bland annat av beskrivande frågor, skattningsfrågor och attitydfrågor.

Syfte:

Syftet med studien är att ta fram och analysera trafiksäkerhetsstatistik.
Trafiksäkerhetsenkäten 2009
TS-enkäten 2009
Keywords: drinking behaviour; alkoholvanor; road traffic; vägtrafik; speed limits; fartgräns; protective headwear; skyddshjälmar; road accidents; trafikolyckor; road safety; trafiksäkerhet; cyclists; cyklister; child safety; barnsäkerhet; traffic regulations; trafikbestämmelse; bicycles; cyklar; transport safety; transportsäkerhet; breathalyser testing; alkoholtest; traffic; trafik; safety equipment; säkerhetsutrustning; road users; vägtrafikanter; velocity; hastighet; vehicle restraint systems; bilens inre säkerhet; traffic offences; trafikförseelse; Legislation and legal systems; Lagstiftning och rättssystem; Children; Barn; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap